MRPC: Maximizing network lifetime for reliable routing in wireless environments - MISRA, Archan (Institutional Knowledge at Singapore Management University, 2002)
We propose MRPC, a new power-aware routing algorithm for energy-efficient routing that increases the operational lifetime of multi-hop wireless networks. In contrast to conventional power-aware algorithms, MRPC identifies the capacity of a node not just by its residual battery energy, but also by the expected energy spent in reliably forwarding a packet over a specific link. Such a formulation better captures scenarios where link transmission costs also depend on physical distances between nodes and the link error rates. Using a max-min formulation, MRPC selects the path that has the largest packet capacity at the 'critical' node (the one with the smallest residual packet transmission capacity). We also present CMRPC, a conditional variant of MRPC that switches from minimum energy routing to MRPC only when the packet forwarding capacity of nodes falls below a threshold. Simulation based studies have been used to quantify the performance gains of our algorithms.